Study On The Draughtability Of Malvi Bullocks - Singh, Brijesh; Nanavati , S.; Joshi , S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted for evaluation of draughtability of Malvi bullocks. A total of 4 Malvi bullocks, aged between 5 to 8 years were evaluated for draught performance. The Overall Draught Ability (ODA) value of 4 Malvi bullocks ranged from 70.48 to 75.20 with an average of 72.31± 0.88. There was a significant (P< 0.01) increase in all the three physiological parameters as compared to their pre-work values. After the completion of work, PCV, Hb and TEC decreased significantly (P < 0.05) but TLC increased significantly (P< 0.01).